Green Finance Strategies for the Zero-Carbon Mechanism: Public Spending as New Determinants of Sustainable Development - Xing, Lining; Li, Jun; Yu, Zhang (Frontiers in Environmental Science, 2022)
A green economy is one that mainstreams nature and people's concerns and produces well-paying jobs for the economy. In the past, researchers examined the relationship between financial growth and carbon emissions. Though, limited studies examined the part of green finance in carbon extenuation. Based on these four indicators, a green finance index is developed in this study: sustainable credit, sustainable safety, sustainable insurance, and sustainable asset. In this study, a vector error correction model (VECM) is used to examine associations between the growth level of green finance, public spending, and the zero-carbon mechanism using data from 2005 to 2018. The findings discovered that China's green finance industry had grown quickly, with enhancements in green finance and increased public spending, all contributing to reducing the country's environmental degradation. The simultaneous increase in carbon intensity slowed the expansion of non-fossil energy usage, reduced the flow of investing in green projects, and finally deteriorated the development of green finance. Furthermore, renewable energy usage in China was chiefly influenced by carbon intensity and green finance, both of which had clear policy-driven consequences. The effects of green finance strategies have consistently fallen short of expectations and have lacked consistency. This study makes recommendations for improving the effectiveness of green finance policy implementation and increasing renewable energy to reduce or erode the economic gains of the zero-carbon mechanism.